2019
DOI: 10.1002/ecs2.2864
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral changes and nutritional consequences to elk (Cervus canadensis) avoiding perceived risk from human hunters

Abstract: The life‐and‐death stakes of predator–prey encounters justify the high price of many anti‐predator behaviors. In adopting these behaviors, prey incur substantial non‐consumptive costs that can have population‐level consequences. Because prey knowledge of risk is imperfect, individuals may even adopt these costly behaviors in the absence of a real threat. For example, rather than only avoid hunters, many species categorically avoid all anthropogenic activity. Although hunting seasons only increase risk for spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 48 publications
1
45
0
Order By: Relevance
“…This is consistent with behavior during summer in previous studies on mule deer in arid climates (Hayes and Krausman 1993, Tull et al 2001, Ager et al 2003, Morano et al 2019), where deer are more active in foraging areas at night and select resting areas with moderate canopy cover during the day (other ungulates, Giotto et al 2013, Long et al 2014). During the rifle season, habitat use by males was not related to density of canopy, but males increased distance from motorized routes, suggesting that avoidance of human activity was a priority behavior, as is true during hunting season in other ungulates (white‐tailed deer [ Odocoileus virginianus ], Kilgo et al 1998; roe deer [ Capreolus capreolus ], Bonnot et al 2013; and elk, Proffitt et al 2013, Paton et al 2017, Spitz et al 2019, Lamont et al 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is consistent with behavior during summer in previous studies on mule deer in arid climates (Hayes and Krausman 1993, Tull et al 2001, Ager et al 2003, Morano et al 2019), where deer are more active in foraging areas at night and select resting areas with moderate canopy cover during the day (other ungulates, Giotto et al 2013, Long et al 2014). During the rifle season, habitat use by males was not related to density of canopy, but males increased distance from motorized routes, suggesting that avoidance of human activity was a priority behavior, as is true during hunting season in other ungulates (white‐tailed deer [ Odocoileus virginianus ], Kilgo et al 1998; roe deer [ Capreolus capreolus ], Bonnot et al 2013; and elk, Proffitt et al 2013, Paton et al 2017, Spitz et al 2019, Lamont et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In general, however, studies in western North America (Conner et al 2001;Vieira et al 2003;Proffitt et al 2009Proffitt et al , 2010Proffitt et al , 2013Ranglack et al 2017;DeVoe et al 2019) have reported habitat shifts toward refugia or security areas during hunting season (Mikle et al 2019, Lamont et al 2020. Specifically, disturbance from hunting can cause animals to move to areas farther from roads (Bonnot et al 2013, Paton et al 2017, DeVoe et al 2019, Spitz et al 2019, with higher canopy cover (Ranglack et al 2017), or restricted public access (Proffitt et al 2009(Proffitt et al , 2010Mikle et al 2019). Consequently, access to quality forage important to autumn nutrition (Cook et al 2004, Tollefson et al 2010, Hurley et al 2014 may be compromised (Benhaiem et al 2008, Spitz et al 2019.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Predator avoidance behavior diverts time and energy away from health and fitness enhancing activities such as foraging, parental care, and mating (Lima, 1998;Frid & Dill, 2002) and can also have consequences for ecosystem functions (Madin et al, 2010;Rizzari et al, 2014). The application of a predation risk framework may help to interpret the extent to which underwater survey counts reflect actual abundances vs a behavioral bias (Frid, McGreer & Frid, 2019), the costs of avoidance behavior on body condition and reproduction (Spitz et al, 2019), and how these factors (together with fishery removals) may influence the results of SDMs.…”
Section: Introductionmentioning
confidence: 99%
“…Predator avoidance behavior diverts time and energy away from health and fitness enhancing activities such as foraging, parental care, and mating (Lima 1998, Frid andDill 2002) and can also have consequences for ecosystem functions (Madin et al 2010, Rizzari et al 2014. The application of a predation risk framework may help to interpret the extent to which underwater survey counts reflect actual abundances vs a behavioral bias (Frid et al 2019), the costs of avoidance behavior on body condition and reproduction (Spitz et al 2019), and how these factors (together with fishery removals) may influence the results of SDMs.…”
Section: Introductionmentioning
confidence: 99%